Pregnancy in lymphangioleiomyomatosis: clinical and lung function outcomes in two national cohorts. Issue 10 (11th August 2020) - Taveira-DaSilva, Angelo M; Johnson, Simon R; Julien-Williams, Patricia; Johnson, Jan; Stylianou, Mario; Moss, Joel
Abstract : Pregnancy in women with lymphangioleiomyomatosis (LAM) has been associated with increased complications and worsening lung function although objective data to advise patients are not available. We assessed lung function and CT scans before and after pregnancy in 16 women with LAM. During the pregnancy, pneumothorax was frequent and mean forced expiratory volume in 1 s (FEV1 ) fell from 77%±19% prepregnancy to 64%±25% predicted and DLCO from 66±26 to 57±26 (both p<0.01). After pregnancy, rates of FEV1 decline were high and 10 patients required sirolimus. Women with LAM, especially with moderate or advanced disease should be counselled regarding adverse events and loss of lung function during the pregnancy.